Individual corporate reputation and perception of collective corporate reputation regarding stock market investments. - Anna Blajer-Gołębiewska (Public Library of Science (PLoS), 2021)
There are two different concepts of corporate reputation grounded in individual and collective perceptions, respectively. The aim of this study was to identify how these two ways of conceiving of corporate reputation affect investors' decisions about whether or not to buy stock in a given company. As this problem tackles individual decision-making processes, we designed and applied an incentivised economic experiment based on vignette studies and focused on individual decisions of single investors. Subjects took part in an online game that imitates stock exchange conditions and that concerns corporate reputation and investing. We found that the individual propensity to invest is not directly based on an investor's perception (rooted in historical share price and other objective metrics) of a firm's reputation but rather on an investor's subjective recognition of collective corporate reputation in the market. This suggests a need to rethink the popular measures of corporate reputation in the context of studies of stock market investor decisions.